THE ROLE OF GREEN SATISFACTION IN MEDIATING THE INFLUENCE OF GREEN IMAGE ON GREEN LOYALTY(Study of Domestic Tourists Staying at Puri Wirata Dive Resort and Spa Amed) - I Putu Wahyudiatmika Putra; Ni Made Asti Aksari (Adisam Publisher, 2024)
In a growing business world, awareness towards the importance of the environment as a major factor in marketing activities is increasing. Many businesses now not only see the environment as a social responsibility, but also as an important element in designing their marketing strategies. This phenomenon will encourage businesses to create products and services that not only benefit customers, but are also sustainable for the environment. This research was conducted at Puri Wirata Dive Resort and Spa Amed. This study looked at how green satisfaction, for domestic visitors staying at Puri Wirata Dive Resort and Spa Amed, mediates the effect of green image on green loyalty. The sample in this study were 110 respondents. Data collection was carried out by distributing questionnaires via Google form. The collected data were analyzed with classical assumption test, path analysis technique, Sobel test and VAF test. The study's findings show that, for domestic visitors staying at Puri Wirata Dive Resort and Spa Amed, green image has a positive and significant effect on green loyalty, green satisfaction has a positive and significant effect on green loyalty, and green satisfaction is able to partially mediate the effect of green image on green loyalty. The implications of this research can be used for Puri Wirata Dive Resort and Spa Amed to make policies to increase green loyalty by maximizing green image and green satisfaction.